ANALISIS KREATIVITAS SISWA DALAM MEMBUAT KARYA KOLASE DI KELAS II SEKOLAH DASAR NEGERI 188 PEKANBARU - Mismeidi; Zariul Antosa; Zufriady (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Creativity is an important ability that needs to be developed from an early stage of elementary education. However, students' creativity in visual arts learning still requires attention, as some students experience difficulties in developing ideas and producing diverse works. This study aimed to describe the creativity of second-grade students at State Elementary School 188 Pekanbaru in creating collage artworks and to identify the factors influencing their creativity. The study employed a descriptive quantitative approach involving 20 second-grade students as research subjects. Data were collected through observation, performance assessment, documentation, and interviews. Students' creativity was measured based on four indicators: fluency, flexibility, originality, and elaboration. The data were analyzed using mean scores, standard deviation, and creativity level categorization. The results showed that students' creativity improved in each collage learning session. The mean creativity score in the first meeting was 70.62 (moderate category), increased to 80.00 (moderate category) in the second meeting, and reached 84.06 (high category) in the third meeting. Improvements were observed across all creativity indicators, with elaboration showing the highest increase. Factors influencing students' creativity included internal factors such as interest, imagination, and self-confidence, as well as external factors including the teacher's role, learning methods, freedom of expression, and the use of varied materials and media. Therefore, collage-based learning was proven effective in developing elementary school students' creativity.